PENINGKATAN MENULIS TEKS DISKUSI MENGGUNAKAN PENINGKATAN MENULIS TEKS DISKUSI MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI SMP NEGERI 2 PONTIANAK - Dewi, Rossa Sari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â  Abstract The research problem of this study is, how the process and learning outcomes of student in discussion text by using problem based learning models in VIII C class in the academic year 2016/2017. The purpose of this study was to describe the planning; implementation and evaluation of learning proses in writing discussion text by using the problem based learning model in VIII C class in the academic year 2016/2017. This Action Research was conducted in two cycles as below. this study showed that the average of studentsâ€™ learning outcome before doing classroom action research was 66.64, and the result of students writing by using problem based learning model in the first cycle showed an improvement on the average of students learning outcome that was 75.48 and the result on the second cycle was 79.10.Based on this study, the researcher suggest the teacher in SMP Negeri 2 Pontianak can take the advantage of problem based learning model that increase students participation in teaching learning process and pay attention on the shortage of this learning model. Keywords: Writing Skill, Discussion Tekt, Problem Based Learning